Loading rate effects on infrasound characterization of uniaxial compression damage in marble - Yanbo ZHANG; Bo WANG; Peng LIANG; Xulong YAO; Guangyuan YU; Zhigang TAO (Meitan xuebao)
Low-frequency infrasound signals are distinguished by minimal energy attenuation and robust penetration capabilities, endowing them with notable advantages for non-contact monitoring of rock fracture. In order to investigate the relationship between infrasonic signal characteristics and loading rate during rock instability failure, uniaxial compression infrasonic monitoring tests were conducted on marble at four different loading rates. The gathered infrasound signals underwent denoising, and the dominant frequency as well as energy parameters of the infrasound were extracted utilizing Fast Fourier Transform and Wavelet Packet Transform. The characteristics of the dominant frequency and energy of infrasound in marble were studied, the influence of loading rate on the dominant frequency and energy of infrasound in marble was analyzed, and the precursor warning criterion of marble instability damage was proposed based on the maximum energy of infrasound. The results showed that: The dominant frequency of marble infrasonic waves exhibited distinct band-like evolution patterns under different loading rates, primarily distributed within six frequency bands: 1 Hz, 2 Hz, 3 Hz, 4 Hz, 5 Hz, and 6 Hz. With the increase of the loading rate, the main frequency strip changes from dense to sparse, and the 6 Hz main frequency strip will gradually disappear. The dominant frequencies at 2 Hz and 4 Hz were significantly influenced by the loading rate effect, there was a decrease in proportion for the dominant frequency at 2 Hz while an increase for that at 4 Hz occurred. Consequently, there was a shift in advantage dominant frequency from 2 Hz to 4 Hz. Marble infrasonic waves displayed evident surge phenomena during the plastic stage under various loading rates, and with the emergence of maximum energy. With increasing loading rates, both maximum energy and cumulative energy of infrasonic wave decreased progressively. The calm period following emergence of maximum infrasonic energy could be utilized as a precursor feature indicating marble instability and failure occurrence. With increasing loading rates, the stress level corresponding to the maximum infrasonic energy is becoming closer to the peak stress, the duration of the calm period is shorter. A precursor criterion for marble instability damage based on infrasound energy ratio is proposed, and the critical value of the precursor criterion decreases gradually with the increase of loading rate.